A comparative study of depiction of feminism on Indian celluloid in pre and post-liberalisation era: tribute to a visionary maestro. (3rd June 2020) - Mukherjee, Arunava Narayan; Mukherjee, Kana; Mukherjee, Aindrila
Media, particularly cinema, plays a significant role in constructing the image of women in today's world. Over past decades, Indian cinema has witnessed a major transformation in the way women are portrayed through films. Both Pink - a recent Hindi movie and Adalat O Ekti Meye - a Bengali movie made in early 1980s have very carefully pictured the deliberate demeaning of woman as mere object of desire. This research makes a comparative study between the pre-liberalisation and post-liberalisation era on the portrayal of women in celluloid with reference to the role of cine-star, who otherwise helps in the branding of a movie. These visual texts under study have critiqued the patriarchal systems as being perpetrators of crime against women and the complicity that consolidates women's peripheral status as secondary sex. However, due to differences in context, audience, advertisement strategies, cast and most importantly people's level of acceptability between the two movies, they were acknowledged differently.